The ecophysiological characterisation of terroirs in Stellenbosch : the contribution of soil surface colour - Witbooi, Erna Hailey (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScAgric (Viticulture and Oenology))--Stellenbosch University, 2008.